Typology Standards for Educators and Educational Personnel in Islamic Education to Optimize the Educational Process - Bilal Dzakawali; Ratu Suntiah; Taupik Hamdani; Tian Septian (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Education is a major factor in the progress of a nation and the development of individuals and society. The urgency of optimizing education needs to be considered from two sides, namely from the side of an educator and educational staff, an educator has a major role in education, however there are several competency problems within an educator, namely, the low ability of educators to control the class, low innovation and creativity carried out to create creative and enjoyable learning. The necessary efforts are to improve the quality of educators by restoring an educator's awareness of the standards that must be met, and grouping the types of educators so that the educational process becomes more optimal. This type of research is library research, which studies various books, journals and previous similar research results, which are useful for obtaining a theoretical basis for the problem to be studied. The conclusion of this article is the importance of standards and typologies of educators and educational staff in Islam in efforts to achieve an optimal educational process.